2017
DOI: 10.1002/slct.201702437
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Green Reduction for Graphene‐Silver Nanocomposite Using Betel Leaf Extract for the Photocatalytic Degradation of Water Pollutants

Abstract: Green leaves are utilized in the green synthesis of various nanomaterials as these are rich sources of various biomolecules useful to control the growth of nanoparticles and as reducing agents. In this report, the in situ synthesis of a nanocomposite of silver decorated on reduced graphene oxide sheets using betel leaf extract as stabilizing and reducing agent is presented. The formation of nanocomposite is confirmed by Ultraviolet‐Visible, Fourier Transform Infrared and Raman spectroscopic techniques. The X‐R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Wherein, the addition of AgNPs leads to the formation of a new energy level which reduces the band gap energy and prolongs the recombination of eÀ h + . [52] Therewithal, AgNPs play the role of an electronic adaptor from the electron-hole separation of TiO 2 semiconductors while the existence of UV irradiation. However, instead of the transmission from CB to VB directly, these electrons are moved to owe to the mobility of the AgNPs and displaced on the surface of the graphene sheets.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Wherein, the addition of AgNPs leads to the formation of a new energy level which reduces the band gap energy and prolongs the recombination of eÀ h + . [52] Therewithal, AgNPs play the role of an electronic adaptor from the electron-hole separation of TiO 2 semiconductors while the existence of UV irradiation. However, instead of the transmission from CB to VB directly, these electrons are moved to owe to the mobility of the AgNPs and displaced on the surface of the graphene sheets.…”
Section: Chemistryselectmentioning
confidence: 99%
“…However, the nanocomposite can degrade 95 % of methylene blue dye in 2 hrs, photocatalytically. [68] The separation step can be further upgraded by making the nanocomposite magnetic as for example GO-Fe 3 O 4 /PAA/Ag (where PAA = polyallylacid and GO = graphene oxide). [69] Incorporation of silver nanoparticles into semiconductor metal oxide such as TiO 2 can overcome the demerits associated with large band gap and hence improve the photocatalytic activity.…”
Section: Dye Degradation By Silver Nanocompositementioning
confidence: 99%
“…Chandu et al reported in Graphene-and Graphene Oxide-Bounded Metal Nanocomposite for Remediation of Organic… DOI: http://dx.doi.org/10.5772/intechopen.92992 situ synthesis of a nanocomposite of silver decorated on reduced graphene oxide sheets using betel leaf extract as a stabilizing and reducing agent. The sheet structure of reduced graphene oxide and uniformly distributed 28 nm silver nanoparticles exhibited good photocatalytic efficiency (95% in 2 h) against methylene blue in sunlight [35]. In another paper, Chandu et al efficiently synthesized graphene oxide sheets decorated with silver nanoparticles (CRG-Ag nanocomposite) in 12 h using custard apple leaf extract, and as-synthesized CRG-Ag nanocomposite showed excellent photocatalytic efficiency of 96% in 2 h under sunlight using methylene blue (5 mg/L) as a model pollutant [36].…”
Section: Photocatalytic Degradation Of Dyesmentioning
confidence: 99%